PENGARUH PENYULUHAN GIZI TENTANG PENTINGNYA SARAPAN TERHADAP PENGETAHUAN ANAK REMAJA - Dinda Afriani Putri (CV. Adiba Aisha Amira, 2024)
There are many types of nutritional problems that Indonesian teenagers face and require medical attention. Breakfast is defined as food eaten before or at the beginning of the day, within two hours after waking up. The aim of this research is to find out how parents pay attention to the nutritional development of their teenage children through breakfast every day. The research design is survey and outreach based, meaning that information is collected using a questionnaire. The samples taken were 50 parents or mothers. The data obtained is in the form of calculation results through filling out a questionnaire. The research results show that one of the external variables that influences children's eating habits is their parents. Apart from teaching and modeling good lifestyle behavior, preparing a balanced nutritional menu and serving healthy food can help the younger generation develop a healthy lifestyle. It is also important for them to understand the importance of a balanced nutritional diet. The conclusion of this research is that a person's level of nutritional knowledge has a significant influence on the way they search for food or make eating decisions, both of which influence how much nutrition they consume.